Optimal Controller Design of Legless Piezo Capsubot Movement. (14th February 2013) - Farahani, Alireza Ahangarani; Suratgar, Amir Abolfazl; Talebi, Heidar Ali
This paper presents an optimal control method based on control effort minimization for a legless piezo capsubot. The capsubot is an underactuated nonlinear dynamics system which is driven by an internal impact force and friction. Here, the motion mechanism of the capsubot is divided into two stages. In the first stage, the aim is to design an optimal controller minimizing energy consumption. In the second stage, optimization is not an objective and instead a four-step strategy for inner mass of the capsubot is proposed. Then, based on the proposed motion strategy, a trajectory profile is given. Using this trajectory profile, the capsubot moves in the desired direction. To evaluate the performance of the proposed control scheme, a comparative study has been performed by means of simulation. Simulation results show that the proposed approach is promising as compared to the Open-Loop Control (OLC) approach and Close-Loop control (CLC) approach which are widely used in the literature for control of capsubots.